Optimizing interval training at power output associated with peak oxygen uptake in well-trained cyclists - Rønnestad, B. R.; Hansen, J. (The Journal of Strength and Conditioning Research, 2016)
The purpose of this study was to investigate the acute physiological responses of interval protocols using the minimal power output (MAP) that elicits peak oxygen uptake (VO2peak) as exercise intensity and different durations of work intervals during intermittent cycling. In randomized order, 13 well-trained male cyclists (VO2peak = 67 ± 6 ml/kg/min) performed 3 different interval protocols to exhaustion. Time to exhaustion and time = 90% of VO2peak were measured with MAP as exercise intensity, and work duration of the intervals equals either 80% of Tmax, 50% of Tmax, or 30 seconds with recovery period being 50% of the work duration at intensity equal to 50% of MAP. The major findings were that the interval protocol using 30-second work periods induced longer time =90% of VO2peak and longer work duration at MAP intensity than the interval protocols using work periods of 50% of Tmax or 80% of Tmax (p = 0.05). There was no difference between the protocols using work periods of 50% of Tmax or 80% of Tmax. In conclusion, the present study suggests that the 30-second work interval protocol acutely induces a larger exercise stimulus in well-trained cyclists than the protocols using work periods of 50% of Tmax or 80% of Tmax. The practical application of the present findings is that fixed 30-second work intervals can be used to optimize training time at MAP and time =90% of VO2peak in well-trained cyclists using MAP exercise intensity and a 2:1 work:recovery ratio.